2011
DOI: 10.1615/critreveukargeneexpr.v21.i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Context Dependent TCF/LEF Expression and Function: Alternative Tales of Repression, De-Repression and Activation Potentials

Abstract: Wnt signaling controls cell specification and fate during development and adult tissue homeostasis by converging on a small family of DNA binding factors, the T-cell factor/lymphoid enhancer factor (TCF/LEF) family. In response to Wnt signals, TCF/LEF members undergo a transcriptional switch from repression to activation mediated in part by nuclear β-catenin binding and recruitment of co-activator complexes. In mammals, the specificity and fine tuning of this transcriptional switch is also achieved by the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 244 publications
3
68
2
1
Order By: Relevance
“…Thus, MAPK signaling can influence Wnt target gene activation by regulating the protein stability of isoforms of TCF4 transcription factors. It has been shown that changes in the relative abundance of Tcf4 variants can indeed fine tune target gene expression in a cell-context-dependent manner (47). Because the Tcf4M/S proteins can bind β-catenin, we assume that by reducing these isoforms by MAPK inhibition, more β-catenin becomes accessible for canonical Wnt target gene activation through the large Tcf4E transcription factor.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, MAPK signaling can influence Wnt target gene activation by regulating the protein stability of isoforms of TCF4 transcription factors. It has been shown that changes in the relative abundance of Tcf4 variants can indeed fine tune target gene expression in a cell-context-dependent manner (47). Because the Tcf4M/S proteins can bind β-catenin, we assume that by reducing these isoforms by MAPK inhibition, more β-catenin becomes accessible for canonical Wnt target gene activation through the large Tcf4E transcription factor.…”
Section: Discussionmentioning
confidence: 98%
“…TCF7 and LEF1 regulate transcription initiation by forming a coactivating complex with nuclear β-catenin. P53 and the nuclear receptor family may inhibit the Wnt signaling pathway by regulating TCF7/LEF1 activation or repression (38). AXIN2 (39) and MYC (40) are the targets in the classic Wnt signaling pathway, which modulates the stability of β-catenin to regulate cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…CAL-101 and Indo blocked Akt phosphorylation and β-catenin expression in Th17 cells, but only temporarily, as these pathways rebounded to a greater extent (compared with untreated cells) after secondary antigen recall responses. Th17 cells treated with both drugs expressed higher lev- els of Tcf7, a critical protein in the Wnt/β-catenin pathway responsible for promoting T cell self-renewal (3,37,(41)(42)(43)(44). Moreover, the treated Th17 cells reexpressed β-catenin and phosphoAkt upon restimulation in vivo.…”
Section: Discussionmentioning
confidence: 98%